Unusual Gingival Enlargement: A Rare Case Report - Ashutosh Dixit; Seema Dixit; Pravin Kumar (Case Reports in Dentistry)
This is an atypical case report of a 20-year-old male patient who suffered from unusual unilateral, gingival enlargement together with rapidly progressive alveolar bone loss. The enlarged gingiva completely covered his left posterior teeth in both arches. The patient was diagnosed with gingival fibromatosis and aggressive periodontitis based on the clinical, histological, and radiographic findings. The gingival enlargement was treated by conventional gingivectomy under local anaesthesia. The postoperative result was uneventful.